Perceptions of child body size and health care seeking for undernourished children in southern Malawi - Flax, Valerie L. (Qual Health Res, 2015)
Child undernutrition affects millions of children globally, but little is known about the ability of adults to detect different types of child undernutrition in low-income countries. We used focused ethnographic methods to understand how Malawian parents and grandparents describe the characteristics they use to identify good and poor child growth, their actual or preferred patterns of health seeking for undernourished children, and the perceived importance of child undernutrition symptoms in relation to other childhood illnesses. Malawians value adiposity rather than stature in assessing child growth. Symptoms of malnutrition, including wasting and edema, were considered the least severe childhood illness symptoms. Parents delayed health care seeking when a child was ill. When they sought care, it was for symptoms such as diarrhea or fever, and they did not recognize malnutrition as the underlying cause. These findings can be used to tailor strategies for preventing and treating growth faltering in Malawian children.